2017
DOI: 10.33102/sainsinsani.vol2no2.45
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Wakaf Dan Cinta Kemanusiaan Untuk Kesejahteraan Umat

Abstract: Islam is aimed at fulfilling all demands of life. Waqf is one of the elements considered as a gift to the community. Waqf included in the aspects of philanthropy and love of humanity and respect each other because it is a part of the concerns towards fellow Muslims. In addition to that, philanthropy also links humanity love as a basis of peace of all nations. However, current discussions on humanitarian or philanthropic remains opaque among Muslims. Using qualitative methods in a thematic analysis of Waqf, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tolerance is the attitude of human beings who are open minded and easily forgive towards other people without voicing negative words regardless of their tribe, race and religion (Ramly et al, 2018). Lastly, the value of Affection is a warm gentle feeling of caring and loving someone regardless of their age and status (Hasbani et al, 2017) As a result, it is believed that these three USMVs can help Malaysia's Arabic curriculum achieve the objectives of the National Education Philosophy. This matter became a priority because it was found that the Arabic Language textbooks taught from elementary school through university did not reflect the aspects of USMV, despite the fact that Arabic Language is synonymous with the al-Quran which is loaded with values.…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance is the attitude of human beings who are open minded and easily forgive towards other people without voicing negative words regardless of their tribe, race and religion (Ramly et al, 2018). Lastly, the value of Affection is a warm gentle feeling of caring and loving someone regardless of their age and status (Hasbani et al, 2017) As a result, it is believed that these three USMVs can help Malaysia's Arabic curriculum achieve the objectives of the National Education Philosophy. This matter became a priority because it was found that the Arabic Language textbooks taught from elementary school through university did not reflect the aspects of USMV, despite the fact that Arabic Language is synonymous with the al-Quran which is loaded with values.…”
Section: Introductionmentioning
confidence: 99%